Problem of pollution of soils heavy metals - IvashchenkoО.О.; IvashchenkoО.О.; AndreevV.О. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2017)
An important environmental issue today is the accumulation of toxic their metals in soils. On the basis of analyzed literary sources shown to be the most polluted territory of our state is the urbanized square of the central and the south-eastern regions. Among metal-pollutants of the soil are the most widespread and toxic nets, zinc, copper, cadmium, nickel and aluminum. Mobility and bioavailability heavy metals and aluminum is directly proportional to the acidity of the soil.Taking into account the potential hazard of toxic metals for living organisms The urgent task of scientists is to assess the biological risk these substances. The article analyzes the accumulation of lead compounds (Pb) and nickel (Ni) soil fields adjacent to the highway Kyiv-Odessa, on different distances from the source of pollution.